Using Direct Decarbonization Strategies to Plan for a Resilient and Fossil Fuel-Free Future - Kelli O'Day; Carla Fresquez (Universitas Diponegoro, 2024)
UC Davis has a vision for a fossil fuel-free future. The university released the Fossil Fuel-Free Pathway Plan (FFFPP) to address the climate crisis by reducing Scope 1 and Scope 2 greenhouse gas emissions. The FFFPP outlines strategies to eliminate 95% of fossil fuel use, based on 2019 levels, from university operations by 2040. The plan includes the Davis campus, UC Davis Health, Aggie Square, Tahoe Environmental Research Center, Bodega Marine Laboratory, and multiple outlying and leased properties. UC Davis has already broken ground on the Big Shift, a fossil fuel-free conversion project that will allow the campus to heat buildings with electricity rather than natural gas and reduce the Davis campus’s fossil fuel consumption by 80%. The FFFPP aligns with broader climate goals and initiatives set by the University of California (UC). The Pathways to a Fossil-Free UC Task Force was created to investigate the challenge of accelerating efforts to decarbonize each UC campus. To further support these efforts the UC recently adopted stronger climate action goals that prioritize direct emission reductions. UC Davis participates in the UC President’s Bonnie Reiss Leading on Climate Student Fellowship Program, which funds student-generated projects that reinforce the UC-wide climate action goals. UC Davis students in the program are playing an important role in climate resiliency on campus.